A Logical Approach for Real Time Big Data Analytics on Heterogeneous Nosql Databases - HAJOUI, Omar; Talea, Mohamed (International Journal of Engineering and Technology, 2018)
NoSQL databases are developed to provide a set of new big data management features while overcoming certain limitations of relational databases. However, these databases are heterogeneous; they provide different mechanisms for storing and retrieving data, which directly affect the performance, consistency and availability of data. In addition, they offer different models of data storage, different implementations, query languages and APIs. This wide variety of platforms makes data interoperability difficult. Data interoperability can be defined as the ability of an application to interact at the same time with a set of different and heterogeneous systems. The goal of our research is to design a new approach that makes it easy for applications to analyze and explore data stored in multiple NoSQL databases. Our approach is based on a Meta model for transforming data from one model to another. Also, we have developed a common API that hides the access specificities of each NoSQL database while allowing the transformation of this data into JSON format.Â Â